Study and Development of Process Material Fiber Board from Sugar Cane Leaf in Applied Product Design for Sugar Cane from Agriculturist Thai - Songwut Egwutvongsa; Somchai Seviset (My University, 2016)
This research has objectives as this following: 1) to study the properties and quantities of the leave-buds and the leaves of sugar cane 2) to develop the transformation process of the leave-buds and the leaves of sugar cane as the materials replacing of wood 3) to test the replacing material standard from using the leave-buds and the new transformed leaves of sugar cane 4) To take satisfaction assessment to manufactured process and the transformation steps of the leave-buds and the leaves of sugar cane as the materials replacing of the wood.According to above details, it was found as this following: 1) for the peeling of tissues on the leave-buds and the leaves of sugar cane, it has applied with the caustic soda, water and salt by boiling with fire in 100 Celsius.Similarly, for the leave-buds it can boil with fire for totals 40 minutes while the leave stalks of sugar cane should be boiled for totals 60 minutes.2) for the sheet forming , it has applied the Isocyanate Resins with 7 percent and tissues from materials replacing of wood with 93 percent by using the sheet of sugar cane replacing of wood with the size of 45 cm X 120 cm as using the hot rolling process in 130 Celsius and pressure for 180 kilograms per square meter.3) for the test result with Japanese standard of JIS A 5908-1994, it had the specific gravity of 0.74 and the property of moistness quantity with 9.75 percent that have been in the benchmark level and in the modulus of rupture or MOR standard, it had the result with level of 6.53 and in modulus of elasticity or MOE standard, it had the result with level of 327.76 MPa that haven't been in the benchmark level.4) for the satisfaction assessment of manufactured process and transformation steps of the leave-buds and the leaves of sugar cane, it has showed that the effectiveness of the material process replacing of wood from the leave-buds and the leaves of sugar cane was in average level of 4.14.
Keywords: Sugar cane; Cane; Mechanical Engineering and Vibrations Research